PERILAKU BULLYING VERBAL PADA PESERTA DIDIK KELAS IX SMP LKIA PONTIANAK - Kurnia Kurnia; Indri Astuti; Abbas Yusuf (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This research was about Verbal Bullying Behavior to 9th Grade Students of SMP LKIA Pontianak. The problems in this research are: (1) what are the causes of an individual being bullied verbally? (2) What are the effects of verbal bullying for victims? (3) What are the effects of verbal bullying on perpetrators? (4) How is the BK teacher’s effort in addressing victims of verbal bullying? (5) How is the BK teacher’s effort in preventing verbal bullying acts committed by the students? This study aims to describe and find out about the forms of verbal bullying behavior that occurred to 9th grade students of SMP LKIA Pontianak.Based on the results of this study, it was shown that verbal bullying to 9th grade students of Pontianak LKIA Middle School was in a fairly high category. (1) Family factors as the main cause of individuals doing verbal bullying with the category "fairly high" has a percentage of 70%. (2) Loneliness is the impact of verbal bullying "quite high" with a percentage of 70%. (3) The highest impact for perpetrators of verbal bullying which will be excluded from school with a percentage of 66% to the "quite enough" category. (4) BK teacher effort to prevent verbal bullying with the highest percentage of 71% was to create a social context with the category of "high enough". (5) Efforts of the BK teacher in overcoming the victims of "quite high" verbal bullying with a percentage of 67% were by working with the school and parents. Keywords:  Students, Verbal Bullying.